Strategies of Livestock Feeding and Health Management in Arid Regions of India - Mathur, B K (Annals of Arid Zone, 2016)
The total bovine population in India which includes cattle, buffalo, mithun and yak is 299.9 million in 2012 census and shows a decline of 1.57% over previous census. However, the number of cows and buffaloes in milk has increased from 77.04 million to 80.52 million showing a growth of 4.51% in India. This emphasizes the need of strategic scientific feeding and health management of livestock. Since the country is facing shortage of dry roughages, concentrates and green fodder, we have to look for alternate feed resources like fibrous crop residues, non-conventional feed resources monsoonal weeds to cope up with the feed requirement in arid zone. High fibre crop residues and non-conventional feeds may be subjected to various processing methods such as physical, chemical and biological treatments for their effective utilization. Supplementation of mineral mixtures and common salt is also essential for proper utilization of feeds. Arid zone is registering continuous and increased prevalence of many epidemiologically important diseases of animals which includes prevalent infectious, non-infectious, parasitic, deficiency and production diseases and also toxicity which are of economic importance. These diseases need careful and timely management to assure good health and sustenance of the production. Sustainable integrated farming system models should be developed for different situations to achieve region-wise balance of livestock, environment and human needs. Key words: Livestock, feeding, health management.